Deep-water hydroids (Cnidaria: Hydrozoa) of Galicia (NW Spain), exclusive of Plumularioidea - Costas-Pérez, Javier; Rey, Alán; Gil, Marta; Ramil, Fran (Zootaxa, 2026)
This report focuses on the benthic hydroids, exclusive of Plumularioidea McCrady, 1859, collected during two oceanographic surveys carried out in deep waters off Galicia (NW Spain) in 2004 and 2009. A total of 31 species belonging to 20 genera and 14 families of the order Leptothecata Cornelius, 1992 were identified. The families Zygophylacidae Quelch, 1885, Lafoeidae Hincks, 1869, Sertulariidae Lamouroux, 1812 and Haleciidae Hincks, 1869, each with four species, were the most specious. Zygophylax levinseni (Saemundsson, 1911), Stegopoma bathyale Vervoort, 1966, Egmundella grimaldii Leloup, 1940, Acryptolaria conferta (Allman, 1877) and Acryptolaria conferta minor Ramil & Vervoort, 1992 are reported for the first time from Galician waters. The known bathymetric range for Cuspidella grandis Hincks, 1869, A. conferta minor, Obelia geniculata (Linnaeus, 1758) and Halecium marocanum Billard, 1934 is extended. The eurybathic condition of the Galician hydroids studied herein is remarkable, with their bathymetric ranges exceeding 300 m. Biogeographical contingents included two main groups: species with a wide distribution (60%) and Atlantic species (37%). Nearly half of the species (48.39%) were collected from bottoms represented by hard substrates.